Self-Efficacy vs Career Maturity: Quantitative Findings Among College Students - Ishlakhatus Sa'idah (Advice: Jurnal Bimbingan dan Konseling, 2024)
This study aims to determine the relationship between self-efficacy and career maturity in Islamic Guidance and Counseling Education (BKPI) students of IAIN Madura. Using a quantitative approach with a correlational method, this study involved 80 students of the 2020 intake. We collected data using two scales: a career maturity scale (27 items, = 0.887) and a self-efficacy scale (14 items, = 0.811). Data analysis was carried out using Spearman's rank correlation. The results showed a significance value of 0.045 (<0.05) and a correlation coefficient of 0.225, which indicated a positive and significant relationship between self-efficacy and career maturity. This means that the higher the self-efficacy, the higher the career maturity of students. Conversely, low self-efficacy is related to low career maturity. The conclusion of this study is to accept the alternative hypothesis (Ha).